Acute effects on pulmonary function in young healthy adults exposed to traffic-related air pollution in semi-closed transport hub in Beijing. Issue 5 (September 2016) - Huang, Jing; Deng, Furong; Wu, Shaowei; Zhao, Yan; Shima, Masayuki; Guo, Bin; Liu, Qichen; Guo, Xinbiao
Abstract Objectives Transport hub is an important part of urban comprehensive transportation system. Traffic- related air pollution can reach high level because of difficulty of diffusion and increase of emission in transport hub. However, whether exposure in this semi-closed traffic micro-environment causes acute changes in pulmonary function of commuters still needs to be explored. Methods Forty young healthy adults participated in this randomized, crossover study. Each participant underwent 2 h exposure in a designated transport hub and, on a separate occasion, in an appointed park. Personal exposures to fine particulate matter (PM2.5 ), black carbon (BC) and carbon monoxide (CO) were measured. Forced expiratory volume in 1 s (FEV1 ) and peak expiratory flow (PEF) were assessed pre-, during and post-exposure. Mixed linear models were used to analyze the pulmonary effects of traffic-related air pollutants. Results Participants had significantly higher exposures to PM2.5, BC and CO in the transport hub than in the park. Exposure in transport hub induced significant reductions in FEV1 and PEF compared with the park during exposure 1 and 2 h. The reductions were significant associated with traffic-related air pollutants. For instance, per 10 μg/m3 increment in PM2.5 was associated with −0.15 % (95 % CI −0.28, −0.02 %) reduction in FEV1 during exposure 2 h. However, effects became attenuate after 2 h exposure. Conclusions Short-term exposure in transport hub had acute reduction effects on pulmonary function. More attention should be paid to the health effects of exposure in the semi-closed traffic micro-environment.